AIR POLLUTION FROM THE PHOSPHORUS COMBUSTION - Biliaiev, M. M.; Shakina, O. P.; Shmihel, O. Yu. (Science and Transport Progress, 2007)
The 3D numerical model to simulate the toxic gas dispersion during phosphor firing.The model is based on the K-gradient transport model. The results of numerical experiment are presented.